IPCC emission scenarios: How did critiques affect their quality and relevance 1990–2022?. (July 2022) - Pedersen, Jiesper Tristan Strandsbjerg; van Vuuren, Detlef; Gupta, Joyeeta; Santos, Filipe Duarte; Edmonds, Jae; Swart, Rob
Graphical abstract: Highlights: We review the evolution of emission scenarios 1990–2022 via 280 emission scenario critiques & responses. Critiques comprise four key categories: assumptions and ranges (scenario substance), methods and user relevance. Critiques became increasingly influential since 2000, enhancing scenarios and their credibility. The intergovernmental exclusion of mitigation scenarios 1992–2010 compromised scientific credibility. IPCC critique disappeared after 2011, while convergence & probability discussions decreased. Abstract: Long-term global emission scenarios enable the analysis of future climate change, impacts, and response strategies by providing insight into possible future developments and linking these different climate research elements. Such scenarios play a crucial role in the climate change literature informing the Intergovernmental Panel on Climate Change's (IPCC) Assessment Reports (ARs) and support policymakers. This article reviews the evolution of emission scenarios, since 1990, by focusing on scenario critiques and responses as published in the literature. We focus on the issues raised in the critiques and the possible impact on scenario development. The critique (280) focuses on four areas: 1) key scenario assumptions (40%), 2) the emissions range covered by the scenarios and missing scenarios (25%), 3) methodological issues (24%), and 4) the policy relevance and handling of uncertainty (11%). Scenario critiques have become increasingly influential since 2000. Some areas of critique have decreased or become less prominent (probability, development process, convergence assumptions, and economic metrics). Other areas have become more dominant over time (e.g., policy relevance & implications of scenarios, transparency, Negative Emissions Technologies (NETs) assumptions, missing scenarios). Several changes have been made in developing scenarios and their content that respond to the critique.